Digital humanities as third culture - Hunter, Andrea (MedieKultur: Journal of media and communication research, 2014)
Th is article examines collaboration in the digital humanities through a sociological lens, focusing on the social relations, including hierarchies, that form in the digital humanities. It argues that the digital humanities can be seen as a form of third culture (Snow, 1971) in which people from computing science and the humanities form new relationships and in some cases move towards an embodiment of third culture. While the humanities are still seen as largely driving the digital humanities, there is increasingly recognition of the importance of technology and programmers. Significant strides are being taken towards involving those with computing and technical expertise in the design and conception of the digital humanities although this transition is not always smooth or democratic.